Extent of application mathematics teachers The international quality standards in teaching Field study in the public schools in Lattakia City (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to identify the degree of application of the total quality standards are applied in the teaching of mathematics in the schools of Lattakia and the degree of availability of the educational environment to be applied in light of the variables: (experience, qualification, gender) in the schools of the official secondary schools, The research also followed the descriptive approach. The final sample consisted of (100) mathematics teachers and school teachers in the secondary  schools of Lattakia. The questionnaire was used as a tool to collect the data needed to answer the research questions. The following statistical methods were used:-Pearson coefficient to measure the correlation between the adequacy of the criteria and their suitability.- Alpha Kronbach coefficient to measure the stability of the research tools.- Duplicates and percentages, mean arithmetic and standard deviation.- Test (t).- One way ANOVA testThe research found a number of results, the most important of which are the following: the degree of availability of the total quality standards in the teaching of mathematics in the secondary schools of Lattakia is medium according to the views of the teachers. and the research has a high level of assessment and testing in the secondary schools of Lattakia. The study also found that the level of educational devices in the Lattakia schools is weak and that the school library and its contents are weak in both Arabic and English. This indicates the weak level of the educational environment required to implement international quality standards in the teaching of mathematics.In light of the research results, the researcher made a number of recommendations, the most important of which are: Conduct a similar study in the rest of the Syrian Arab Republic schools and conduct similar studies in relation to the rest of the teachers such as physics, chemistry, science, languages.The research also recommended supporting schools with material and financial resources to improve the educational environment in terms of: (classrooms, laboratories, teaching aids and devices, school library) In concrete terms.